RARE CASE OF OVARIAN STEROID CELL TUMOR NOT OTHERWISE SPECIFIED IN A POSTMENOPAUSAL WOMAN - Bitoska, Iskra; Plaseski, Toso; Jovanovska Mishevska, Sasha; Shubeska Stratrova, Slavica; Todorova, Biljana; Muca, Argjent; Stojovska Jovanovska, Elizabeta; Krstevska, Brankica (Journal of Morphological Sciences; Vol 5 No 2 (2022): JMS, 2022)
Ovarian steroid cell tumors, not otherwise specified (NOS), are rare ovarian sex cordâ€“stromal tumors with malignant potential. They represent less than 0.1% of all ovarian neoplasms. Little is known about this tumor, it is rare, and only a small number of case reports are available in the literature. This type of tumor can  produce testosterone, leading to hyperandrogenism, virilization and amenorrhea. Postmenopausal occurrences are rare. We present  a 60-year-old woman with onset of virilization, worsening alopecia and excessive growth of hair on abdominal and genital parts of the body. She has elevated levels of adrenal androgens. Radiologic studies were consistent with left sided ovarian changes. A diagnostic and therapeutic bilateral salpingo-oophorectomy confirmed steroid cell tumor NOS in both ovaries. Post-operatively, the patient had complete resolution of her symptoms and normalization of testosterone levels. Keywords : ovarian steroid cell tumor, ovarian neoplasma, hyperandrogenism, virilization.